2023
DOI: 10.5551/jat.63725
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Diabetes Mellitus and Serum Lathosterol and Campesterol Levels: The CACHE Study DM Analysis

Abstract: Aim: Risk of cardiovascular disease is increased in patients with diabetes mellitus (DM). Cholesterol metabolism (hepatic synthesis and intestinal absorption) is known to be associated with cardiovascular risk. Next, we examined the association of DM with cholesterol absorption/synthesis. Methods:The CACHE Consortium, which is comprised of 13 research groups in Japan possessing data of lathosterol (Latho, synthesis marker) and campesterol (Campe, absorption marker) measured by gas chromatography, compiled the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 52 publications
0
4
1
Order By: Relevance
“…In addition, there is inconsistency as for the link between diabetes and cholesterol absorption in previous studies [35,36]. Matsumura et al reported that diabetes associated with lower cholesterol absorption independently [14]. However, we did not find a correlation between diabetes and cholesterol absorption or synthesis in this study.…”
Section: Discussioncontrasting
confidence: 82%
See 1 more Smart Citation
“…In addition, there is inconsistency as for the link between diabetes and cholesterol absorption in previous studies [35,36]. Matsumura et al reported that diabetes associated with lower cholesterol absorption independently [14]. However, we did not find a correlation between diabetes and cholesterol absorption or synthesis in this study.…”
Section: Discussioncontrasting
confidence: 82%
“…Cholesterol synthesis can be assessed by measuring serum levels of lathosterol, a precursor of cholesterol [11]. Previous studies have indicated that various clinical factors, such as age, sex, obesity, hypertension, diabetes, renal dysfunction, and lipid-lowering medications, are associated with serum sterol levels [12][13][14][15][16]. Understanding the impact of these clinical factors on cholesterol metabolism and oxysterol levels in patients with CAD is of great importance.…”
Section: Introductionmentioning
confidence: 99%
“…High levels of lathosterol can indicate increased cholesterol synthesis in the body [26]. In patients with T2D, the plasma level of campesterol is reported to be low [27], whereas a higher lathosterol profile is found [28].…”
Section: Discussionmentioning
confidence: 99%
“…High levels of lathosterol can indicate increased cholesterol synthesis in the body [ 26 ]. In patients with T2D, the plasma level of campesterol is reported to be low [ 27 ], whereas a higher lathosterol profile is found [ 28 ]. In the present study, we demonstrated that campesterol and lathosterol turnovers also exist in HFD-fed rats, while dietary HMT rice flour attenuated this fluctuation.…”
Section: Discussionmentioning
confidence: 99%
“…These complementary actions may explain the favorable effects of statin-ezetimibe combination therapy. Diabetes mellitus has been associated with low levels of cholesterol absorption markers 27) . Considering the mechanism of ezetimibe, the levels of cholesterol absorption marker may affect the LDL-C lowering effect.…”
Section: Limitationmentioning
confidence: 99%